1033 Endobronchial Sclerotic Neurofibroma: A Case Report of a Very Rare Benign Tumour. (12th October 2021) - Iftikhar, S; Youssef, S; Gey Van Pittius, D; Ghosh, S; Haris, M
Abstract: Introduction: Endobronchial neurofibromas are exceedingly rare benign lesions most commonly originating at the trachea. Primary pulmonary tumours of neurogenic origin such as peripheral nerve sheath tumours (PNSTs) are extremely rare, accounting for less than 0.2% of all lung tumours. Intrathoracic PNSTs are usually benign and are commonly found in the posterior mediastinum as schwannomas with female preponderance. We present the first reported occurrence of the sclerotic variant of endobronchial neurofibroma and the approach used in its definitive investigation and management. Case Report: A 69-year-old Caucasian male with a 66 pack-year smoking history and a background of alcohol induced liver cirrhosis, peripheral vascular disease and dilated cardiomyopathy presented with dyspnoea and fatigue with severe normocytic anaemia. Computed Tomography (CT) chest, abdomen and pelvis revealed an indeterminate nodule at the secondary carina projecting into the bronchus intermedius (BI). Fibreoptic bronchoscopy showed a polypoid lesion with a vascular appearance. Under general anaesthetic, combined fibreoptic and rigid bronchoscopy was used to remove the lesion with rigid forceps. Gross histological appearance showed an 8x6x5mm pedunculated lesion with a 2mm diameter short stalk and histology of a sclerotic neurofibroma with fibroblasts and collagen, positively staining for S100 and LP10. This patient is due for follow up in 6-month with a CT chest to ensure no tumour recurrence. Conclusions: Endobronchial neurofibromas appear highly vascular and demand extra caution at bronchoscopic intervention. Prompt, experienced thoracic surgical and intervention pulmonology input should always be sought. Combined approach of fibreoptic and rigid bronchoscopy allows better control of potential bleeding and the airway.